Answer: y = (x-2)/3
This is equivalent to y = (1/3)x - 2/3
=================================================
To get this answer, we need to swap x and y in the original equation. Then solve for y to get the inverse.
y = 3x+2
x = 3y + 2 ... x and y swapped
x-2 = 3y
3y = x-2
y = (x-2)/3
y = x/3 - 2/3
y = (1/3)x - 2/3
This final equation has slope 1/3 and y intercept -2/3
Answer:
there is no pictures. so there for i can not answer your question
Your using the distributive property in your example, hope that helps.
Answer:
Y = -3x - 1
Step-by-step explanation:
Y= mx + b
M is the slope
Y is the y intercept